Detrimental effects on executive function and mood following consecutive days of repeated high-intensity sprint interval exercise in trained male sports players. Issue 7 (3rd April 2022) - Costello, Sarah E.; O'Neill, Barry V.; Howatson, Glyn; van Someren, Ken; Haskell-Ramsay, Crystal F.
ABSTRACT: Intensified periods of competition are common in many team sports, potentially leading to increased fatigue and reduced performance. The purpose of this study was to investigate the effect of repeated high-intensity sprint interval exercise on cognitive function, mood and perceptions of energy and fatigue. Twenty-four trained rugby players completed multiple bouts of repeated sprints across two consecutive days. Prior to and following each set of maximal effort sprints or equivalent control duration, a battery of cognitive tasks assessing simple and choice reaction time, visuo-spatial working memory and inhibition were completed as well as visual analogue scales that assessed mood, energy, and fatigue. Accuracy of incongruent Stroop responses was significantly lower across day 2 compared to day 1 and the control condition. Four-choice reaction time was slower across day 2 whilst feelings of alertness, contentedness, and physical and mental energy were reduced while ratings of physical and mental fatigue increased. These findings suggest that intensified periods of high-intensity sprint interval exercise have detrimental effects on executive function, mood and perceptions of physical and mental energy, and fatigue. These deleterious effects have the potential to impact performance and may increase the propensity for injury/accidents in certain sporting and non-sporting contexts.